1992
DOI: 10.1126/science.256.5060.1172
|View full text |Cite
|
Sign up to set email alerts
|

Designed Enediynes: A New Class of DNA-Cleaving Molecules with Potent and Selective Anticancer Activity

Abstract: The rational design and biological actions of a new class of DNA-cleaving molecules with potent and selective anticancer activity are reported. These relatively simple enediyne-type compounds were designed from basic chemical principles to mimic the actions of the rather complex naturally occurring enediyne anticancer antibiotics, particularly dynemicin A. Equipped with locking and triggering devices, these compounds damage DNA in vitro and in vivo on activation by chemical or biological means. Their damaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
98
0
3

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 312 publications
(101 citation statements)
references
References 58 publications
0
98
0
3
Order By: Relevance
“…Several analogues were also made by using the same approach. In the following years, copious synthetic and SAR studies of enediyne analogues of the dynemicin core were performed by the groups of Schreiber,61a,61d Wender,63 Nicolaou,61b, 64 Isobe,65 Myers,62a, 66 Danishefsky,61g, 67 Maier,68 Magnus,69 and others 64a,64d, 70. These studies probed the effects of triggering groups or initiators on the nitrogen atom or aryl ring, which could be activated under basic or photochemical conditions that could be mimicked by intracellular processes.…”
Section: Natural Product Derived Fragments In Drug Discoverymentioning
confidence: 99%
“…Several analogues were also made by using the same approach. In the following years, copious synthetic and SAR studies of enediyne analogues of the dynemicin core were performed by the groups of Schreiber,61a,61d Wender,63 Nicolaou,61b, 64 Isobe,65 Myers,62a, 66 Danishefsky,61g, 67 Maier,68 Magnus,69 and others 64a,64d, 70. These studies probed the effects of triggering groups or initiators on the nitrogen atom or aryl ring, which could be activated under basic or photochemical conditions that could be mimicked by intracellular processes.…”
Section: Natural Product Derived Fragments In Drug Discoverymentioning
confidence: 99%
“…CalC-Á1 belongs to enedyine family of antibiotics and these molecules (23,24) are similar in size and structure to known substrates of the MDR1-Pgp. Early studies conducted in drug-sensitive/resistant cell pairs with mAb-linked CalC-Á1 indicated a modulating effect of MDR1-Pgp on cytotoxicity (19).…”
Section: Resultsmentioning
confidence: 99%
“…1A), representative of a class of enediyne glycoconjugate DNA ligands, binds to and cleaves DNA at specific 4-bp sequences. Double-strand DNA cleavage occurs through bioreduction of the trisulfide and subsequent 1,4-benzenoid diradical formation, which results in hydrogen abstraction from adjacent nucleotide bases (10)(11)(12)(13). Affinity cleavage experiments (7,8) demonstrate that CLM preferentially cleaves DNA at cytosine-containing homopyrimidine tracts, preferentially TCCT.…”
mentioning
confidence: 99%